INTERACTION OF MACROECONOMIC VARIABLE SHOCKS AND MONETARY POLICY INTERVENTIONS ON THE PROFITABILITY OF SHARIA COMMERCIAL BANKS IN INDONESIA - Mohammad Aliman Shahmi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Background. Economic growth and financial development in Indonesia are supported by developments in the Islamic banking industry. The business continuity of Islamic banking is determined by financial performance, which is measured by the level of profitability. The profitability of Islamic commercial banks is thought to be influenced by macroeconomic variables and monetary policy interventions.Purpose. This study aims to analyze the effect of shocks on macroeconomic variables, including the real effective exchange rate and consumer price index, and monetary policy intervention through the policy instrument of the Indonesian central bank's benchmark interest rate, namely the BI Rate, and the effect of the capital adequacy ratio on the profitability of Islamic commercial banks in Indonesia in the short and long term.Method. This study employs error-correction model analysis to completely utilize secondary data from January 2015 to May 2022. Data gathered from the Financial Services Authority's (OJK) Sharia Banking Statistics and Fred Economic Data (FED)Results. The research results show that the real effective exchange rate and consumer price index affect the profitability of Indonesian commercial banks in the long term but do not have a significant effect on the profitability of Islamic commercial banks in the short term. Monetary policy does not have a significant effect in the short or long term. Meanwhile, the capital adequacy ratio has a significant influence on the profitability of Islamic commercial banks in the short and long term.Conclusion. Macroeconomic variable shocks have the ability to disrupt banking performance in the short term, and this situation shows that banking management has not put flexible policies and a strategic approach to short-term changes in place. Short-term changes are still managed from the standpoint of handling internal conditions, however management is fairly effective at controlling capital adequacy.